MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN DI KOTA YOGYAKARTA - , Fahrini Yulidasari; , Prof. dr. Hamam Hadi, MS, Sc. D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Stunting is growth disorder commonly found in children of under 24 months. The prevalence of stunting children under five at the Province Yogyakarta Special Territory is 22.5% and at Yogyakarta Municipality is 15.11%. The prevalence of stunting in children uedr 24 months is associated with many factors, such as breastfeeding cessation leading to early complementary breastfeeding supplementation, inadequate nutrient intake (energy and protein) and social economic condition of the family. Objective: To analyze risk of complementary breastfeeding to the prevalence of stunting in children of 6-24 months at Yogyakarta Municipality. Method: The study was observational with case control study design. Location of the study were three subdistricts (Tegalrejo, Umbulharjo and Kota Gede) at the area of Yogyakarta Municipality. Subject of the study were children of 6-24 months at Yogyakarta Municipality. Samples consisted of 121 stunting and 121 non stunting children selected through non probability sampling with consecutive sampling method. Status of stunting in children was assessed through height/age and analysis of risk of complementary breastfeeding to the prevalence of stunting. The study also observed education of parents, members of the family, low family income, birth weight, parentsâ height as external variables related to complementary breastfeeding. Result: The prevalence of stunting was higher in children of 13-24 months (80.2%) male (52.1%). The result of bivariate analysis showed the time of complementary breastfeeding supplementation was significantly associated with the prevalence of stunting (OR = 1.71